Strengthening Local Security Governance: A Study of Public Order and Community Protection Management in Manahan Urban Village, Surakarta - Joko Pramono (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to examine the effectiveness of community security and order (Kamtibmas) management at the village level, with a specific case study in Manahan Sub-district, Banjarsari District, Surakarta City. A qualitative approach was employed using a case study design to explore the issue in a holistic and contextual manner. The study involved key stakeholders, including village officials, Linmas personnel, Babinsa, Bhabinkamtibmas, and community representatives, selected through snowball sampling. Data were collected through in-depth interviews, participant observation, and documentation. The data analysis used the interactive model of Miles, Huberman, and Saldaña (2014), and findings were interpreted using Steers’ organizational effectiveness framework, which includes the goal approach, system approach, and resource-based approach. The results show that the security management system remains suboptimal in achieving its goals, with weak coordination, limited resource support, and fragmented community participation. Informal citizen-led activities such as night patrols are not integrated into the official security framework, reflecting an untapped potential of community-based security governance. The conclusion highlights the need for structured coordination mechanisms, improved resource allocation, and the institutionalization of citizen involvement. It is recommended that local governments formulate a spatially informed security master plan, enhance the capacity of Linmas personnel, and adopt digital tools for reporting and monitoring. Further studies are encouraged to explore technology integration in grassroots-level public safety systems and conduct cross-regional comparisons to develop adaptive governance models.